Phospholipase C zeta profiles are indicative of optimal sperm parameters and fertilisation success in patients undergoing fertility treatment. (20th May 2020) - Kashir, Junaid; Mistry, Bhavesh V.; BuSaleh, Lujain; Abu‐Dawas, Reema; Nomikos, Michail; Ajlan, Ahmed; Abu‐Dawud, Raed; AlYacoub, Nadya; AlHassan, Saad; Lai, F. Anthony; Assiri, Abdullah M.; Coskun, Serdar
Abstract: Background: Oocyte activation is driven by intracellular calcium (Ca 2+ ) oscillations induced by sperm‐specific PLCζ, abrogation of which causes oocyte activation deficiency in humans. Clinical PLCζ investigations have been limited to severe male infertility conditions, while PLCζ levels and localisation patterns have yet to be associated with general sperm viability. Materials and Methods: PLCζ profiles were examined within a general population of males attending a fertility clinic (65 patients; aged 29‐53), examining PLCζ throughout various fractions of sperm viability. Male recruitment criteria required a minimum sperm count of 5 × 10 6 spermatozoa/mL, while all female patients included in this study yielded at least five oocytes for treatment. Sperm count, motility and semen volume were recorded according to standard WHO reference guidelines and correlated with PLCζ profiles examined via immunoblotting and immunofluorescence. Appropriate fertility treatments were performed following routine clinical standard operating protocols, and fertilisation success determined by successful observation of second polar body extrusion. Results and Discussion: Four distinct PLCζ patterns were observed at the equatorial, acrosomal + equatorial regions of the sperm head, alongside a dispersed pattern, and a population of spermatozoa without any PLCζ. Acrosomal + equatorial PLCζ correlated most to sperm health, while dispersed PLCζ correlated to decreased sperm viability. Total levels of PLCζ exhibited significant correlations with sperm parameters. PLCζ variance corresponded to reduced sperm health, potentially underlying cases of male sub‐fertility and increasing male age. Finally, significantly higher levels of PLCζ were exhibited by cases of fertilisation success, alongside higher proportions of Ac + Eq, and lower levels of dispersed PLCζ. Conclusions: PLCζ potentially represents a biomarker of sperm health, and fertilisation capacity in general cases of patients seeking fertility treatment, and not just cases of repeated fertilisation. Further focused investigations are required with larger cohorts to examine the full clinical potential of PLCζ.